Total energy expenditure and nutritional intake in continuous multiday ultramarathon events - Best, A. W.; McGrosky, A.; Swanson, Z.; Rimbach, R.; McConaughy, K.; McConaughy, J.; Ocobock, C.; Pontzer, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2023)
Continuous multiday ultramarathon competitions are increasingly popular and impose extreme energetic and nutritional demands on competitors. However, few data have been published on energy expenditure during these events. Here, we report doubly labeled water-derived measures of total energy expenditure (in kilocalories per day) and estimated physical activity level (PAL: total energy expenditure/basal metabolic rate) collected from five elite and subelite finishers (four males and one female, age 34.6 ± 4.9 years)—and nutritional intake data from the winner—of the Cocodona 250, a ~402-km race in Arizona, and from a fastest-known-time record (one male, age 30 years) on the ~1,315-km Arizona Trail. PAL during these events exceeded four times basal metabolic rate (Cocodona range: 4.34-6.94; Arizona Trail: 5.63). Combining the results with other doubly labeled water-derived total energy expenditure data from ultraendurance events show a strong inverse relationship between event duration and PAL (r2 = .68, p < .0001). Cocodona race duration was inversely, though not significantly, associated with PAL (r2 = .70, p = .08). Water turnover varied widely between athletes and was not explained by PAL or body mass. The Cocodona race winner met ~53% of energy demand via dietary intake, 85.6% of which was carbohydrate, while ~47% of energy demand was met via catabolism of body energy stores. Together, these results illustrate the energetic deficits incurred during competitive continuous multiday ultramarathon efforts and implicate macronutrient absorption and/or storage as key factors in ultramarathon performance.